Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/bi990605b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Folding Pathways of Large Cyclic Polypeptides:  Studies of the Cystine Knot Polypeptide Kalata B1

Abstract: Kalata B1 is a member of a new family of polypeptides, isolated from plants, which have a cystine knot structure embedded within an amide-cyclized backbone. This family of molecules are the largest known cyclic peptides, and thus, the mechanism of synthesis and folding is of great interest. To provide information about both these phenomena, we have synthesized kalata B1 using two distinct strategies. In the first, oxidation of the cysteine residues of a linear precursor peptide to form the correct disulfide bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
265
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(276 citation statements)
references
References 25 publications
10
265
0
1
Order By: Relevance
“…However, a significant proportion of correctly folded peptide was obtained from the linear precursor when oxidation reactions were performed in the presence of organic solvents. A hydrophobic solution environment appeared to be required to stabilize the surface-exposed hydrophobic residues that are formed upon folding into the native conformation (12). Furthermore, hemolytic activity was observed for cyclized kalata B1 but not for the oxidized linear derivative (12).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…However, a significant proportion of correctly folded peptide was obtained from the linear precursor when oxidation reactions were performed in the presence of organic solvents. A hydrophobic solution environment appeared to be required to stabilize the surface-exposed hydrophobic residues that are formed upon folding into the native conformation (12). Furthermore, hemolytic activity was observed for cyclized kalata B1 but not for the oxidized linear derivative (12).…”
mentioning
confidence: 97%
“…The circulins were found in a screen for anti-human immunodeficiency virus activity (8), cyclopsychotride A inhibits neurotensin binding to cell membranes (9), and kalata B1 shows uterotonic activity (6,10). Violapeptide I (11) was originally discovered based on its hemolytic activity, and it has recently been shown that kalata B1 (12,13), the circulins (12,13), and cyclopsychotride A (13) also have relatively weak hemolytic activity. A large number of additional peptides from this family have recently been discovered.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4] It is believed that the compact CCK motif of cyclotides is responsible for their exceptional resistance against chemical, thermal, and proteolytic degradation. [5] Cyclotides display a diverse range of biological activities, including uterotonic, [6] haemolytic, [7][8][9] neurotensin antagonistic, [10] HIV inhibitory, [11] antimicrobial, [12] cytotoxic, [13] antifouling, [14] and trypsin inhibitory activities. [15] In addition, kalata B1 and B2 have been shown to inhibit the growth and development of Helicoverpa punctigera and H. armigera larvae, suggesting that cyclotides function as insecticidal agents as part of plant defence systems.…”
mentioning
confidence: 99%